The Implementation of Covid-19 Security Protocols in City of San Fernando, Pampanga - Lucaylucay, Dory Jr; Barawid, John Michael; Gutierrez, John Luis; Macaspac, Jesus Jr; Perez, Sean Mael; Pine, Clark Shane; Saipen, George Jr. (Web of Journals Publishing, 2023)
The first case of the Novel Corona Virus came from the reports from the health officials in Wuhan, China in the late part of 2019. Retrospective investigations by Chinese authorities have identified human cases with onset of symptoms in early December 2019. The first reported cases of the virus are said to have links in the wet market of Wuhan city, where majority of the first patients were known to have an association with this market. They are either the store keepers, or customers or just a mere visitor in the place, the reported samples taken in December 2019 revealed, which led to a conclusion that it was in this place that the outbreak started. This prompted the Chinese government to close the market place in the early 2020. Coronavirus is a zoonotic virus causing illness that may range from an ordinary cold to a more serious respiratory disease. Covid-19 is the most recent to make the jump to human infection.